Impact of obstacles on transmission efficiency of magnetic coupling resonant wireless power transmission system - TIAN Zijian; DU Xinxin; ZHU Yuanzhong; WANG Juan (Gong-kuang zidonghua, 2015)
Requirements of coal mine underground were analyzed for wireless power energy transmission. Characteristics of three kinds of wireless power transmission technologies were researched including microwave type, electromagnetic induction and magnetic coupling resonant type as well as their applicability in coal mine underground. It was considered that magnetic coupling resonant type wireless power transmission technology could be applied in coal mine underground. Impacts of different obstacles were analyzed emphatically on transmission efficiency of magnetic coupling resonant wireless power transmission system. A simulation model of magnetic coupling resonant wireless power transmission system was built by using HFSS 3D electromagnetics simulation software, and simulated experiments were carried out using metallic obstacles and the nonmetallic ones. The experimental results show that nonmetallic obstacles have no influence on transmission efficiency of the system, and metallic obstacles reduce transmission efficiency, especially in condition of adding thickness or reducing lateral area of the metallic obstacles.